KAJIAN DAYA SAING SEKTOR PARIWISATA KABUPATEN SAMBAS - Sabahan Sabahan; Yuliansyah Yuliansyah (Politeknik Negeri Batam, 2017)
This study aims to examine the competitiveness of tourism sector Sambas Regency to the surrounding area. The study conducted in the form of analysis of factors that determine the competitiveness of tourism sector of Sambas Regency and the preparation of policy strategies that must be done by regional governments to improve the competitiveness of tourism sector of Sambas Regency. The method of analysis used in this research is the shift share method and composite index. The data used are the number of tourist objects, the number of labor, the number of foreign tourists, the number of domestic tourists, the condition of road circulation, the government budget, the number of hotels, restaurants (restaurants), and travel agencies, and other data related research. Based on the research results, tourism sector in general Sambas Regency has great tourism potential, this is supported by the existence of natural resources, culture and history. Nevertheless, this study shows that Sambas Regency is still experiencing slow growth and less competitive than other areas around Sambas Regency. The most determining factor of tourism competitiveness of Sambas Regency is the supporting and related industry factors, especially the number of restaurants and travel agencies and the number of manpower engaged in tourism is still limited in number. The development of supporting infrastructure and tourism promotion is a condition that must be done by the government in order to improve the competitiveness of tourism sector of Sambas Regency.